Planetary boundaries for recalcitrant materials and toxic chemical pollutants: specifications for sustainable safe operating zones - Ogunseitan, Oladele A. (Frontiers in Environmental Science, 2025)
Announced as “the greatest and most consequential day of deregulation in U.S. history,” 12 March 2025 marks the retreat of the United States Environmental Protection Agency from remedial and preventive policies that were informed by decades of consequential research in environmental science and public health. The USEPA administrator boasted further: “We are driving a dagger straight into the heart of the climate change religion to drive down cost of living for American families, unleash American energy, bring auto jobs back to the U.S. and more.” The retreat threatens science-based regulations that have commanded the attention of researchers, policymakers, healthcare providers, non-governmental stewards of environments and ecosystems, and the general public. An example of such regulations targets mercury pollution, perhaps the only toxic chemical for which a specific UN action, the Minamata Convention, is dedicated. The linkage of mercury emissions to coal combustion as a source of energy that also drives climate change and particulate matter pollution that transcends national boundaries to cause diseases worldwide implies that the adverse impacts of USEPA’s retreat will not be borne only by the US population, but also by the global human population and wildlife. The retreat from progressive agendas on environmental sustainability is not unique to the US. Note the European Commission’s relaxation of reporting rules in the 2025 Competitiveness Compass. We may very well witness a “race to the bottom” as other countries sacrifice environmental regulations in pursuit of corporate profits.